The Important Questions of Statistical Theory of the Crystals’ Thermal and Kinetics Properties - Budzhak, Ya. S.; Wacławski, T. (Physics and Chemistry of Solid State, 2020)
In this paper, the short algorithmic formulas for computations of the crystals thermal and kinetic properties are given. These formulas are fulfilled the case of isotropic crystals for any one of dispersion laws of current carriers, where these carriers can be scattered by all kinds of the crystal lattice defects. In the paper, these algorithmic formulas were used to calculations the important properties of crystals with the nonparabolic Kane’s dispersion law of current carriers. Here, the passing from these non-parabolic dispersion law crystals to the parabolic dispersion law crystals was also described.